School Supervision Improving Learning Quality School Quality in Early Childhood Education - Sumarmi Sumarmi; Sudadi Sudadi (Journal on Education, 2023)
Significant changes are occurring in education. Curriculum constantly adapts needs and daily changes of the world. Maximize education, all the components involved in education must be carried out in accordance with the objectives. All of them have a same goal in achieving citation-matching, which is to prioritize primary education and training. As school partners, supervisors also have a big role in realizing school quality and learning quality. School supervisors are in charge of imparting supervision knowlage. The purpose of this study was to understand effective school supervision practices in order to improve student and school performance. Research employs a kualitatif method with case studies. According to this research, teachers at schools and madrasas should be able to carry out their assigned task of professional supervision; they should also have positive attitudes toward supervising activities and be able to increase student learning outcomes that are carried out in a cooperative manner.